2021
DOI: 10.3803/enm.2021.1132
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Exome Sequencing in Papillary Microcarcinoma: Potential Early Biomarkers of Lateral Lymph Node Metastasis

Abstract: Background: Early identification of patients with high-risk papillary thyroid microcarcinoma (PTMC) that is likely to progress has become a critical challenge. We aimed to identify somatic mutations associated with lateral neck lymph node (LN) metastasis (N1b) in patients with PTMC.Methods: Whole-exome sequencing (WES) of 14 PTMCs with no LN metastasis (N0) and 13 N1b PTMCs was performed using primary tumors and matched normal thyroid tissues.Results: The mutational burden was comparable in N0 and N1b tumors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Hendrix et al demonstrated that the gene RAB27B was associated with metastasis of breast cancer ( Hendrix et al, 2010 ). Other studies have identified mutated genes associated with early recurrence, including FAT3 and USH2A ( Kim et al, 2021 ; Qiu et al, 2021 ). In addition, other researchers have also used multi-omics data to identify biomarkers for cancer recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Hendrix et al demonstrated that the gene RAB27B was associated with metastasis of breast cancer ( Hendrix et al, 2010 ). Other studies have identified mutated genes associated with early recurrence, including FAT3 and USH2A ( Kim et al, 2021 ; Qiu et al, 2021 ). In addition, other researchers have also used multi-omics data to identify biomarkers for cancer recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is little information about their somatic mutations in cancer. Somatic mutations in SLC16A1 [ 18 ], SLC16A7 [ 24 , 64 ], SLC9A2 [ 91 ], SLC9A3 [ 42 ], SLC9A8 [ 48 ], SLC9A9 [ 31 , 85 ], SLC4A2 [ 22 , 88 ], SLC4A4 [ 53 ], SLC4A7 [ 34 ], and SLC4A8 [ 47 ] have been reported in human cancers (Table 1 ). However, their abundance across large pan-cancer cohorts has not been analysed.…”
Section: Pan-cancer Analysis Of Somatic Mutations In Abt-slcsmentioning
confidence: 99%
“…WES has been applied to study PTMC in several cohorts and revealed potential biomarkers and therapeutic targets. 3,4 However, these studies used surgically resected tissue samples, which are typical materials for genetic molecular Liyuan Ma and Luying Gao contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐exome sequencing (WES) is a powerful next‐generation sequencing (NGS) technique that can provide comprehensive information on the genomic landscape of tumors. WES has been applied to study PTMC in several cohorts and revealed potential biomarkers and therapeutic targets 3,4 . However, these studies used surgically resected tissue samples, which are typical materials for genetic molecular testing.…”
Section: Introductionmentioning
confidence: 99%